“Estudio de tiempos para la estandarización de procesos en el área de producción de queso en la empresa lácteos Santa Ivonne de Latacunga” - Gavilanes Yasig, Julio Cesar (2023)
The Dairy Company "Santa Ivonne" is a dairy industry dedicated to the elaboration of different products such as: cheese of different sizes, yogurt and mozzarella cheese, which is categorized within the range of micro-enterprise, nowadays given the imminent competitiveness that In the dairy market, there was a need for companies to be increasingly innovative and in turn have to adopt new technologies, generating new methods to increase their production and thus generate more profits. The present investigation was carried out through a study of times, with a focus on the production sector, because it is the area with the greatest demand, therefore the activities involved in the production process were determined, which an analysis had to be carried out. of times to proceed to optimize and standardize the different stages of cheese manufacturing, the necessary tools that helped to accurately determine the activities were; Cursogramas, flow charts, also through the regression to zero technique of which we take advantage of to find factors such as: the observed time, the normal time, total time, rhythm assessment and the different supplements that in turn served to find the time of cycle with which the current capacity of the company was obtained.